Knowledge wh and False Beliefs: Experimental Investigations. (26th April 2018) - Phillips, Jonathan; George, B R
Abstract: A common approach to knowledge wh is to try to reduce it to knowledge that, and in particular to answer-knowledge. On this view, the truth-conditions of a knowledge wh ascription can be given entirely in terms of which answers to the embedded question the subject knows. Against this background, this paper considers the phenomenon of false-belief sensitivity —a challenge to this common approach to knowledge wh that has recently received a fair amount of attention in the question embedding literature. We present a series of experiments that help bring the empirical standing of this phenomenon into focus. Across six experiments, our results provide evidence that truth judgments of knowledge wh ascriptions are affected by both the presence of false beliefs and the proportion of the subject's beliefs that are false. Collectively, these results demonstrate a pattern of judgments that is incompatible with standard accounts of the relationship between knowledge that and knowledge wh, and with reducibility more generally. After presenting these new data, we end by considering the theoretical implications of this richer descriptive picture and outline a number of remaining open questions that should be pursued in future work.